Rancang Bangun Game Edukasi Caru Rsigana Berbasis Android - Pande Made Satrya Dinata; Putu Wira Buana; Ni Made Ika Marini Mandenni (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2017)
Caru Rsigana is caru undertaken by Hindus to the balance of nature with the Concept of Tri Hita Karana is Parhyangan, Pawongan, and Palemahan. Information about Caru Rsigana usually manifested in a book medium. Game of Caru Rsigana developed as a new innovation infrastructure caru introduction that is implemented in the form of Android-based learning media. Game of Caru Rsigana application built using Corona as system debugging and programming language Lua. This application is a game application stringing or making offerings is needed on Ceremony of Caru Rsigana corresponding to the location, direction of the wind, and color. The Gameplay of Caru Rsigana’s Game created with the concept of drag and drop that is attractive means caru and put in place the appropriate means caru, as well as the time limit specified. Data from the questionnaires Game of Caru Rsigana based on the results of 20 respondents was good, with the percentage Aspects of Visual, Graphics, and Audio amounted to 86.25%, as well as Entertainment and Leisure Aspects of 88.33%.